Characterization and environmental impact analysis of sea land reclamation activities in China. (October 2016) - Duan, Huabo; Zhang, Hui; Huang, Qifei; Zhang, Yukui; Hu, Mingwei; Niu, Yongning; Zhu, Jiasong
Abstract: With rapid urbanization and soaring land prices, many coastal cities in China have turned their eyes to the ocean and built airports or factories on reclaimed land. However, sea land reclamation activities have brought about serious environmental impacts. This study therefore combines qualitative and quantitative information to focus on reclamation activities in China and to highlight the major impacts: eco-system damage and geological disasters, and the deterioration of marine environmental quality resulting from polluted air, water, soil, and sediment. The realized and potential environmental damages are substantial. A resultant policy recommendation is for local Chinese governments to limit land reclamation and to strengthen environmental assessment systems, especially in fragile coastal regions containing important oceanic resources such as mangroves and protected wildlife. Our study can also serve as a reference for the better management of land reclamation in densely populated coastal regions of the world. Graphical abstract: Highlights: Rapid urbanization is threatening to shrink the cities' disappearing coastlines. This study characterizes the reclamation activities and highlights the impacts. From 2012 to 2020, sea reclamation in China mainland would be around 2469 km 2 . The realized and potential environmental damages are substantial. Policy recommendations for sea land reclamation management have been put forward.